(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Purpose: The study aimed to identify the effect of administrative empowerment in enhancing organizational loyalty to administrative employees at a public university, Majmaah University in the Kingdom of Saudi Arabia, as case study. Methodology/ approach: a questionnaire list that included a set of questions; to survey the opinions of those being investigated, and to achieve the aim of the study. Sample and data: An empirical study is conducted on a random sample of (326) administrative employees in various colleges, deanships, and departments of the university. Results: The study found that there is an effect of administrative empowerment through four dimensions (authority delegation, work teams, training, and incentives) in enhancing organizational loyalty among administrative employees at the university under study. It also concluded that there is no effect of the dimension of information sharing in enhancing organizational loyalty from the point of view of the study sample. Among the results of the study, there are also no statistically significant differences at the significance level (0.05) regarding the answers of the respondents regarding the effect of administrative empowerment in enhancing the organizational loyalty of administrative employees at Majmaah University. Originality/value: The study is one of the first studies that addressed the issue of the impact of job empowerment on enhancing job loyalty in public universities, from the point of view of administrative employees. Research limitation/ implication: The study was limited to a sample of administrative employees at Majmaah University with their various titles and job grades.